The mitochondrial dysfunction, alongside the modifiable burden of traditional risk factors, drives the development of early-onset coronary artery disease - Campolo, Jonica; Canale, Paola; Gazzaniga, Gianluca; Parolini, Marina; Piccaluga, Emanuela; Bossi, Irene; Oreglia, Jacopo; Borghini, Andrea; Marinaro, Irene; Andreassi, Maria Grazia (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveMitochondrial dysfunction is associated with increased risk of atherosclerosis by disrupting key cellular processes that contribute to premature vascular ageing. However, the specific role of mitochondrial dysfunction in early-onset coronary artery disease (EOCAD), which is increasing at a particularly alarming rate, remains largely unexplored. This study investigated the association of leukocyte mtDNA-CN and mtDNA4977 deletion with the risk of EOCAD.MethodsThe study included 118 patients (99 men, 51.0 ± 5.6 years) with angiographically EOCAD (≤60 years) and 150 healthy controls (94 men, 49.8 ± 5.8 years). Quantitative RT-PCR was used to quantify mtDNA-CN and mtDNA4977 deletion rate.ResultsThe EOCAD group had a higher prevalence of male gender (p < 0.001), smoking (p = 0.001), hypertension (p < 0.001), diabetes mellitus (p = 0.04) and obesity (p < 0.001) than controls. EOCAD patients had lower mtDNA-CN (p < 0.001) and higher mtDNA4977 deletion (p = 0.026). Low mtDNA-CN levels were significantly associated with male gender (p < 0.001), smoking (p = 0.004), hypertension (p = 0.039), hypercholesterolemia (p < 0.001), and obesity (p < 0.001). Increased levels of the mtDNA4977 deletion were significantly higher in males (p = 0.026) and hypercholesterolemic patients (p < 0.001). The ROC curve of mtDNA-CN and mtDNA4977 deletion in predicting EOCAD showed an AUC of 0.902 (95% CI 0.867–0.937, p < 0.001) and 0.762 (95% CI 0.691–0.834, p < 0.001), respectively. Logistic regression analysis adjusted for confounders showed that both mtDNA-CN and mtDNA4977 deletion were independent significant predictors of EOCAD (p < 0.001 and p = 0.001, respectively).ConclusionsEOCAD is characterized by a high prevalence of modifiable risk factors and mitochondrial damage, underscoring the need for more efforts to reduce the burden of traditional risk factors and highlighting the potential for innovative mitochondrial-targeted therapies.